THE TECHNOLOGICAL LIMITS OF THE RULE OF LAW, AND THE PERSPECTIVE OF DEVELOPING STATES - Lim, Hannah (Indonesia Law Review, 2021)
The 4th industrial revolution and its attendant technologies have given rise to many discussions around the impact of technology on the rule of law. A fundamental premise of the rule of law is that it requires an effective sovereign to establish formal legality. The sovereigns undertaking this responsibility today are states. However, the digital spaces by their very nature challenge the ability of states to do so. Digital spaces present challenges to traditional territorial notions of jurisdiction resulting in their tendency to be “ungoverned”. Ungoverned digital spaces, as with their physical counterparts, are spaces where the rule of law does not operate. Moreover, ungoverned digital spaces can also impact governance in physical spaces. But not all states are equal, and each has unique social contexts to grapple with. Thus, in considering the questions around technology and the rule of law, it is necessary to consider the difference in contexts between states. Such topics are also generally discussed from the perspective of developed and industrialized states, where technology is most extensively developed and deployed. But the impact of the 4th industrial revolution is not limited to the developed world, and communities in developing states constantly engage with such technology, particularly with social media, even if such technology and platforms are developed elsewhere. This paper considers the impact of digital spaces on the rule of law from the perspectives of developing states, focusing on Southeast Asia.